SMALL BUSINESS LENDING AS A GUARANTEE FOR THE DEVELOPMENT OF THE COUNTRY: Ortiqov Ulug‘bek Akrombek o‘g‘li (Ustozlar uchun, 2024)
Lending to small businesses and private entrepreneurship plays an important role in GDP growth and in the development of thecountry's economy.Crediting small business and private business plays main role in increasing GDP and developing economy of the country.